Measurement of multijet azimuthal correlations and determination of the strong coupling in proton-proton collisions at s = 13 TeV - Hayrapetyan,A; Tumasyan,A; Adam,W; Andrejkovic,JW; Bergauer,T; Chatterjee,S; Damanakis,K; Dragicevic,M; Hussain,PS; Jeitler,M; Krammer,N; Li,A; et al. (European Physical Journal C: Particles and Fields, 2024)
A measurement is presented of a ratio observable that provides a measure of the azimuthal correlationsamong jets with large transverse momentum pT . This observable is measured in multijet events over the range of pT = 360–3170 GeV based on data collected by the CMS experiment in proton-proton collisions at a centre-of-mass energy of 13 TeV, corresponding to an integrated luminosity of 134 fb−1 . The results are compared with predictions fromMonte Carlo parton-shower event generator simulations, aswell as with fixed-order perturbative quantum chromodynamics (pQCD) predictions at next-to-leading-order (NLO) accuracy obtained with different parton distribution functions (PDFs) and corrected for nonperturbative and electroweak effects. Data and theory agree within uncertainties. From the comparison of the measured observable with the pQCD prediction obtained with the NNPDF3.1 NLO PDFs, the strong coupling at the Z boson mass scale is αS(mZ) = 0.1177 ± 0.0013 (exp)+0.0116−0.0073 (theo) = 0.1177+0.0117−0.0074 , where the total uncertainty is dominated by the scale dependenceof the fixed-order predictions. A test of the running of αS inthe TeV region shows no deviation from the expected NLOpQCD behaviour.